Childhood obesity among primary school students in Shah Alam / Noor Rodhiah Abd Rahman - Abd Rahman, Noor Rodhiah (2006)
Childhood obesity is a growing health problem among children, locally and internationally. This study was done to determine the prevalence of overweight and obesity among children in Shah Alam and to identify the risk factors probably associated with childhood obesity. A study instrument consisting of questionnaires was constructed based on previous literature done by the San Jose Mercury News/Kaiser Family Foundation and was modified to suit the situation in Shah Alam. 1062 questionnaires were distributed to the students of two primary schools in Shah Alam, Sekolah Kebangsaan Seksyen 7 and Sekolah Kebangsaan Seksyen 9, to be answered by their parents. These questionnaires contained questions regarding the lifestyle of the children in terms of their dietary intake and physical activity, their parents' perceptions on childhood obesity and height and weight of the children to determine their Body Mass Index (BMI). The prevalence of overweight and obesity among children is 13.02% and 14.05%, respectively. Risk factors associated with overweight and obesity in children are found to be non-significant. As a conclusion, the high prevalence of both overweight and obesity among children in Shah Alam prompt further and more accurate study to be done to identify the risk factors truly associated with childhood obesity.